Self-Esteem and Academic Achievement: What are the Explanatory Variabl es among Girls with Hearing Impairment in Selected Secondary Schools f or the Deaf in Kenya? - Bunyasi Awori, Beatrice; K. Karugu, Geoffrey; Kabutha Mugo, John; Aluko Orodho, John (2019)
This study sought to examine the explanatory variables on self-esteem and academic achievement of girls with hearing impairments (HI) in sel ected Secondary Schools for the Deaf in Kenya. The study was guided by Carl Roger's personcentred or client-centred theory. The study used a n ex-post facto research design. Participants for the study were drawn from schools for girls with hearing impairment in Central and Western provinces of Kenya constituting a sample of fifty-three girls. Data w ere collected through questionnaires and interviews and analysed using the Statistical Package for Social Sciences programme. Rosenberg self -esteem scale was used to measure self-esteem dimensions whereas schoo l academic scores were used to measure mean academic achievement. The study revealed that there was a moderate and positive correlation betw een self-esteem and academic achievement of girls with hearing impairm ents. The in-depth interviews indicated that the low achievement of gi rls with hearing impairments could be attributed to current curriculum which was not only less diverse but also that the mode of examination was too conventional and did not take into account the peculiar probl ems of learners with various disabilities The situation could be impro ved through concerted efforts among various education stakeholders. Th us, it was recommended that the Ministry of Education through the Keny a Institute of Curriculum Development should devise a more diverse cur riculum that could be examined through various strategies such as obse rvation and use of sign language. It was further recommended that teac hers should make deliberate use of positive reinforcement techniques g eared towards the promotion of the self-esteem of girls with Hearing I mpairment and encourage them to accelerate their quest to academic per formance